2017
DOI: 10.3945/an.116.012831
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Challenges in Studies Examining the Effects of Breakfast on Cognitive Performance and Appetite in Children and Adolescents

Abstract: Breakfast is purported to confer a number of benefits on diet quality, health, appetite regulation, and cognitive performance. However, new evidence has challenged the long-held belief that breakfast is the most important meal of the day. This review aims to provide a comprehensive discussion of the key methodological challenges and considerations in studies assessing the effect of breakfast on cognitive performance and appetite control, along with recommendations for future research. This review focuses on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 138 publications
(230 reference statements)
0
18
0
Order By: Relevance
“…Thus, this carefully conducted study showed that breakfast consumption had no short-term effect on neuro-psychological functioning in healthy school-age children. More of these studies, along with studies of habitual breakfast consumption, are needed to confirm and extend these results [26] .…”
Section: Breakfast and Neuropsychological Functioningmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, this carefully conducted study showed that breakfast consumption had no short-term effect on neuro-psychological functioning in healthy school-age children. More of these studies, along with studies of habitual breakfast consumption, are needed to confirm and extend these results [26] .…”
Section: Breakfast and Neuropsychological Functioningmentioning
confidence: 96%
“…Firm conclusions about the acute effects of specific breakfast types were unable to be drawn [24] . Subsequent work by these authors reviewed methodological challenges associated with these types of studies [26] . From a systematic review on the effects of breakfast and breakfast composition on cognition in children and adolescents, firm conclusions could not be drawn since there were too few studies, and findings were inconsistent [24] .…”
Section: Breakfast and Neuropsychological Functioningmentioning
confidence: 99%
“…Many studies have shown the proven positive impact of breakfast in appetite regulation [4] and in reducing the risk of type 2 diabetes [53]. Despite all these facts, breakfast is frequently skipped, especially among the young generation, with almost 74% of female students being found to be skipping or irregularly consuming breakfast in Saudi Arabia [48].…”
Section: Introductionmentioning
confidence: 99%
“…The current chapter does not aim to give an exhaustive overview of the literature on all these cognitive domains and how these can be assessed (for reviews, see e.g. Adolphus et al, 2017;Isaacs & Oates, 2008).…”
Section: Introductionmentioning
confidence: 99%